БЕРДАҚ ДӨРЕТИЎШИЛИГИНДЕ ФОЛЬКЛОРЛЫҚ ДƏСТҮРЛЕР - Тоқымбетова, Г.А. (FAN va JAMIYAT, 2016)
The object of the research in the article is Berdakh’s creative work. It studies the use of folklore traditions by the poet. The author’s scientific conclusions on this issue are given. In studying the issue the author follows the works in which literature and folklore issues were analyzed.